Precision Medicine in Graves’ Disease and Ophthalmopathy - Elia, Giusy; Fallahi, Poupak; Ragusa, Francesca; Paparo, Sabrina Rosaria; Mazzi, Valeria; Benvenga, Salvatore; Antonelli, Alessandro; Ferrari, Silvia Martina (Frontiers in Pharmacology, 2021)
Graves’ disease (GD) is a condition caused by an autoimmune process involving the thyroid gland, whose main outcome is hyperthyroidism. TSAb start the autoimmune process stimulating the overproduction of thyroid hormones. In addition, TSAb can stimulate TSH-R expressed in fibroblasts and orbital pre-adipocytes leading to the manifestation of Graves’ ophtalmopathy (GO). Also, autoantibodies directed against IGF-1R have an important role in immune-pathogenesis of GO. Fundamental is the role played by cytokines (IFN-γ, TNF-α, Il-6), and Th1 chemokines in the immune-pathogenesis of both disorders, particularly in the active phase. Novel discoveries in the field led to the investigation of promising therapies, such as immune-therapies towards specific antigens (for example against TSH-R), aiming in restoring the immune tolerance versus the immune dominant epitopes associated with autoimmunity in GD. Moreover, Etanercept (that blocks the TNF-mediated inflammatory responses), TCZ (that acts against the IL-6 receptor), and RTX (that acts against CD20) have proven to be useful and safe therapeutic options in refractory GO treatment. Furthermore, teprotumumab (a human monoclonal anti-IGF-1R blocking antibody), have been revealed effective in the treatment of patients with moderate-severe GO and it is now approved for GO therapy in USA. Molecules able to act as antagonists of CXCR3, or to block CXCL10, are also under study. More extensive researches are needed to deepen out these drugs as well as to identify new targeted and effective therapies, that will permit a more precise identification of GD, or GO, patients able to respond to specific targeted therapies.